Cavity-modified molecular dipole switching dynamics - Weidman, Jared; Dadgar, Mohammadhossein (Shahriyar); Stewart, Zachary J.; Peyton, Benjamin G.; Ulusoy, Inga; Wilson, Angela K. (The journal of chemical physics, 2024)
Polaritonic states, which are formed by resonances between a molecular excitation and the photonic mode of a cavity, have a number of useful properties that offer new routes to control molecular photochemistry using electric fields. To provide a theoretical description of how polaritonic states affect the real-time electron dynamics in molecules, a new method is described where the effects of strong light-molecule coupling are implemented using real-time electronic structure theory. The coupling between the molecular electronic states and the cavity is described by the Pauli-Fierz Hamiltonian, and transitions between polaritonic states are induced via an external time-dependent electric field using time-dependent configuration interaction (TDCI) theory, producing quantum electrodynamics TDCI (QED-TDCI). This method is used to study laser-induced ultrafast charge transfer and dipole-switching dynamics of the LiCN molecule inside a cavity. The increase in cavity coupling strength is found to have a significant impact on the energies and transition dipole moments of the molecule-cavity system. The convergence of the polaritonic state energies as a function of the number of included electronic and photonic basis states is discussed.
Veröffentlicht: 05. März 2024
Gesehen am 12.08.2024